Evaluation of Local Governmet Bureaucracy Reform’s Policy in Pesawaran Regency, Lampung Province, Indonesia - Hairiwira Usman; Wirman Syafri; Sutino Sutino; Diah Puspita (International Journal of Economics Development Research (IJEDR), 2023)
This research aims to (1) understand why bureaucratic reform in the Regional Government of Pesawaran District, Lampung Province has not been successful, and (2) propose an effective model as a recommendation for improving the realization of regional government bureaucratic reform policies in Pesawaran Regency, Lampung Province. The method employed in this research is qualitative, utilizing the theoretical approach of the CIPP Model (Context, Input, Process, and Product) by Stufflebeam to uncover and discuss issues arising from the implementation of Regional Government Bureaucratic Reform Policy Evaluation in Pesawaran Regency, Lampung Province. The study uses qualitative analysis to answer the research problem formulation derived from the execution of the bureaucratic reform policy evaluation in Pesawaran Regency. All data were directly obtained from field informants through interviews and document studies. The results conclude that the bureaucratic reform policy in Pesawaran Regency has not been successful due to the policy implementation being merely formal administrative (context) without the support of a conducive organizational environment (input) and effective governance (process), and the broad scope of bureaucratic reform policy evaluation has not been implemented comprehensively (product). A solution model is proposed for the reasons behind the reform policy failure in Pesawaran Regency, Lampung Province, which includes Leadership, Reward and Punishment, Capability, Systematic and Collaborative approach, Digitalization, Proportional and Consistent efforts, and Responsiveness. These elements should be implemented mutually and inclusively.